O processo magistral de medicamentos em farmácias com manipulação do Estado do Espírito Santo, em cumprimento à legislação específica do setor - Giovanni Margotto Bertollo (2008)
Quality and safety in public health make a binomial that must be reached and maintained, despite economical, regional or operational factors. Medicines are fundamental instruments to guarantee the access to health. Therefore, the quality of compounding medicines must be assured by its producers as it is a right of consumers. This is a challenging issue for compounding pharmacies, mainly due to the particularities associated with the production process of compounded medicines, like the unfeasibility of implementing a quality controlsystem similar to that used in pharmaceutical industries. The aim of the present study was evaluating de degree of suitability of compounding pharmacies in the state of Espírito Santo to the most relevant requirements of Brazilian legislation, including RDC 33/2000 and RDC 214/2006. An epidemiologic transversal experimental design was carried out and an interview guide was elaborated based on regulatory agency inspection checklists in order to collect data about the selected compounding pharmacies. This guide did not supply informationabout quality when used alone. This observation may be due to the simply demonstrative character of the guide regarding the presence of items related to the structure and process, without a qualitative evaluation. Simultaneously to this evaluation, analysis of a medicine selected as a marker of the work quality in pharmacies (finasteride 1 mg capsules) was performed. The analyses of this medicine demonstrated that 80,5% of the evaluated compounding pharmacieswere in agreement with Brazilian regulatory agency requirements.